2017
DOI: 10.25179/tjem.2017-57015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of FTO Gene Alleles on the Diet and Metabolic Risk Factors in the Subjects with Diabetes

Abstract: . The present study is based on a previously published case-control study that indicates the association of different FTO gene with type 2 diabetes. The structured questionnaire was used to gather anthropometric, biochemical, and clinical data. Single nucleotide polymorphism (SNP) in FTO gene was analyzed using Amplication Refractory Mutation System-Polymerase Chain Reaction (ARMS-PCR). The nutritional data were collected using a 24-hour dietary recall questionnaire completed by a trained dietitian. The varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Studies suggest that the genetic profile is likely to affect both dietary habits as well as the association between diet and metabolic syndrome markers. Therefore, it can be concluded that the diet-disease associations are more prominent in individuals having risk alleles AA as compared to protective alleles TT and heterozygous alleles AT as far as FTO gene is concerned [61,62].…”
Section: Fat Mass and Obesity (Fto) Genementioning
confidence: 99%
“…Studies suggest that the genetic profile is likely to affect both dietary habits as well as the association between diet and metabolic syndrome markers. Therefore, it can be concluded that the diet-disease associations are more prominent in individuals having risk alleles AA as compared to protective alleles TT and heterozygous alleles AT as far as FTO gene is concerned [61,62].…”
Section: Fat Mass and Obesity (Fto) Genementioning
confidence: 99%
“…Some recent studies have also revealed its association with HTN in different population. [16][17][18][19] So keeping this in view, it is the need of time to unveil its association with HTN in Pakistani population.…”
Section: Introductionmentioning
confidence: 99%